Dynamic Analysis of Force Redistribution in Small Pile Groups Foundation Subjected to Accidental Lateral Loads - Nathaniel Wilmer, Reynaldo; Adi Prakoso, Widjojo (Jurnal Teknik Sipil, 2024)
Abstract Designing infrastructure always involves considering potential loads. Beyond anticipated loads, accidental ones can occur, as with the Pedamaran II bridge in Riau, where a ship collision damaged its foundation, breaking a pile and cracking the pile cap. However, this did not lead to structural failure, even though over 30% of the piles in the group were damaged. Initial hypotheses suggest that the use of bracing in the existing bridge might have helped redistribute forces. A numerical model was created using Opensees to simulate lateral loading on the shaft of an elevated pile cap, comparing the effects of bracing and no bracing using elastic elements in a simple 2x2 foundation model. The aim was to understand the correct modeling approach for bracing behavior and its impact on load response. Pushover analysis was performed on one of the shafts, with eccentric loading generating forces in both the x and y axes. Results showed that modeling bracing with elastic elements helped evenly distribute forces across rows of piles, with the greatest distribution occurring in the loaded row. The maximum moment occurred at the lowest bracing connection, highlighting the crucial role of bracing in load distribution, and significantly increasing lateral capacity by about 60%.